1999
DOI: 10.1161/01.res.84.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Interleukin-6 Transcription in Vascular Smooth Muscle Cells Through Pleiotropic Activation of Nuclear Factor-κB Transcription Factors

Abstract: —Interleukin-6 (IL-6) is a multifunctional cytokine expressed by angiotensin II (Ang II)-stimulated vascular smooth muscle cells (VSMCs) that functions as an autocrine growth factor. In this study, we analyze the mechanism for Ang II-inducible IL-6 expression in quiescent rat VSMCs. Stimulation with the Ang II agonist Sar 1 Ang II (100 nmol/L) induced transcriptional expression of IL-6 mRNA transcripts of 1.8 and 2.4 kb. In transient transfection assays of IL-6 promoter/luciferase repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
252
1
20

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(285 citation statements)
references
References 43 publications
12
252
1
20
Order By: Relevance
“…Our recent findings also show that BRAP can influence NF-B nucleus translocation, leading to an increase of proinflammatory molecules (unpublished data). In addition, previous studies [27][28][29][30][31][32][33] demonstrated that NF-B can regulate a number of inflammatory genes, including interleukin-6 (IL-6), tumor necrosis factor (TNF), vascular cellular adhesion molecule-1 (VCAM-1), E-selectin, inducible nitric oxide synthase (iNOS), matrix metallo-proteinases (MMPs) and CRP. BRAP was originally identified as a cytoplasmic protein that recognizes the nuclear localization signal of the breast cancer suppressor protein, BRCA-1 1,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings also show that BRAP can influence NF-B nucleus translocation, leading to an increase of proinflammatory molecules (unpublished data). In addition, previous studies [27][28][29][30][31][32][33] demonstrated that NF-B can regulate a number of inflammatory genes, including interleukin-6 (IL-6), tumor necrosis factor (TNF), vascular cellular adhesion molecule-1 (VCAM-1), E-selectin, inducible nitric oxide synthase (iNOS), matrix metallo-proteinases (MMPs) and CRP. BRAP was originally identified as a cytoplasmic protein that recognizes the nuclear localization signal of the breast cancer suppressor protein, BRCA-1 1,34) .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these data, we also found that serum hs-CRP and IL-6 levels were significantly lower by olmesartan than by telmisartan treatment. Angiotensin II is known as one of the main effector peptides inducing IL-6 expression in vascular smooth muscle cells (30,31). In addition, it is well known that IL-6 induces CRP expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-studied VSMCs and macrophages, fibroblasts are also known to inducibly express IL-6 in response to inflammatory cytokines and/or AS [32][33][34][35][36]. Work from our group has shown that IL-6 is a highly inducible gene, a target for direct A-II activation through the ubiquitous NF-κB pathway [32].…”
Section: Discussionmentioning
confidence: 99%